2019
DOI: 10.32995/rev180.num-44.(2019).art-626
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del cambio climático en la zona urbana turística y costera de Viña del Mar: levantamiento de daños para una inundación por marejadas y percepción de seguridad

Abstract: Las ciudades costeras afrontan actualmente diversas problemáticas debido a los efectos del cambio climático. En el caso de la ciudad de Viña del Mar, se visualiza un aumento en la frecuencia e intensidad de eventos de oleaje extremo, por lo que la zona costera será donde este problema tendrá una mayor visibilidad. Este trabajo analiza el impacto de un evento de marejadas en una localidad densamente poblada y visitada por turistas (sector Avenida Perú, Población Vergara, Viña del Mar), así como de la percepción… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…Ainda sobre questões hidrológicas, Igualt et al (2019) discorrem sobre efeitos de mudanças climáticas na zona urbana turística costeira de Viña del Mar, Chile, especificamente sobre ressacas marítimas em localidade densamente povoada e visitada por turistas. Os resultados apontam sensação negativa de segurança frente à constatada necessidade de adaptação da infraestrutura para redução da vulnerabilidade e ampliação da resiliência local.…”
Section: Conteúdos: Compreendendo O Estado Da Arteunclassified
“…Ainda sobre questões hidrológicas, Igualt et al (2019) discorrem sobre efeitos de mudanças climáticas na zona urbana turística costeira de Viña del Mar, Chile, especificamente sobre ressacas marítimas em localidade densamente povoada e visitada por turistas. Os resultados apontam sensação negativa de segurança frente à constatada necessidade de adaptação da infraestrutura para redução da vulnerabilidade e ampliação da resiliência local.…”
Section: Conteúdos: Compreendendo O Estado Da Arteunclassified
“…The Valparaíso region has ~180 km of coastline, of which less than 55% is sandy coastline. The beaches of the region are a national and international tourist attraction [7]. Its coastal morphology is controlled by plate tectonics, configuring an irregular coastline where rocky cliffs, resistant to marine erosion, coexist and form prominent rocky protrusions, sandy beaches, and ancient and contemporary dune fields [8].…”
Section: Study Areamentioning
confidence: 99%
“…Recently, a study carried out in the urban beaches of Valparaíso Bay (Martínez et al, 2018) showed that one beach experienced accretion, two proved to be in stable conditions and one was significantly affected by a shoreline retreat on a decadal scale. Episodic erosion has also been caused by episodic extreme events, which have additionally produced structural damage throughout coastal cities located in Central Chile (Carvajal et al, 2017; Winckler et al, 2017; Igualt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%